PREFERENCES OF UNIPIN MOBILE APPLICATION USING CONJOINT ANALYSIS (CASE STUDY: PT. DUA PULUH EMPAT JAM ONLINE - Marliana Marliana; Natalia Natalia (International Journal of Organizational Business Excellence, 2019)
The purpose of this study is to determine the customers preferencesin developing UNIPIN’s mobile application that can help PT. Dua Puluh Empat Jam Online increases their sales of mobile games vouchers. Data collection methods using questionnaires and interviews on 100 gamers of UNIPIN. The research method used in this study is conjoint analysis which was preceded by Cochran Q-test to test the validity of application attributes and conjoint analysis to know the utility value of each attribute that became the main preference of gamers. The attributes tested include the attributes contained in the 7C Framework such as context, content, community, customization, communication, connection, and commerce. The results of this study are application attributes that can be applied by UNIPIN to increase their sale of mobile game vouchers which are context, content, communication, and commerce attributes. The resultsof this study are attributes that meet the need to develop UNIPIN’s mobile application in order to increase sales in the mobile gaming market are the integrated level of the contex attribute, the product-dominant level of the content attribute, the one-to-one non responding user level of the communication attribute, and high level of commerce.